2019
DOI: 10.1093/rheumatology/key443
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of cartilage damage at the metacarpal head level in rheumatoid arthritis and osteoarthritis: an ultrasound study

Abstract: Objectives. To determine the prevalence and distribution of US-detected qualitative cartilage damage at metacarpal heads of patients with rheumatoid arthritis (RA) and hand osteoarthritis (OA).Methods. Fifty-two RA patients and 34 patients with hand OA were enrolled. US examination of the metacarpal head cartilage from the II to V finger of both hands was performed. A total of 414 metacarpophalangeal (MCP) joints in RA and 266 MCP joints in OA patients were scanned with a linear probe up to 22 MHz.Qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Compared to the commonly affected DIP, PIP, and thumb base joints, radiographic findings in MCP joints are relatively uncommon in hand OA, as demonstrated in the population-based Framingham study (11). Nevertheless, a recent study applying ultrasound to assess cartilage in a small cohort of RA and hand OA patients found the MCP joints to be commonly affected in hand OA and with similar prevalence as in RA (247).…”
Section: Mrimentioning
confidence: 98%
“…Compared to the commonly affected DIP, PIP, and thumb base joints, radiographic findings in MCP joints are relatively uncommon in hand OA, as demonstrated in the population-based Framingham study (11). Nevertheless, a recent study applying ultrasound to assess cartilage in a small cohort of RA and hand OA patients found the MCP joints to be commonly affected in hand OA and with similar prevalence as in RA (247).…”
Section: Mrimentioning
confidence: 98%
“…US examinations were carried out using a MyLab Class C (Esaote SpA, Genoa, Italy), equipped with a very high-frequency broadband linear probe (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). A grayscale standard setting was adopted (B-mode frequency: 22 MHz, master gain: 70%, mechanical index: 0.3, dynamic range: 12, depth 15 mm, focus position at the area of interest).…”
Section: Us Image Acquisition and Interpretationmentioning
confidence: 99%
“…The accuracy of conventional radiography has been questioned in non-weight-bearing joints such as the ones of hands and wrists, which are commonly involved in different rheumatic diseases (3,4). Moreover, in several studies, conventional radiography was found to be less sensitive than ultrasonography (US) in the detection of joint damage (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this minimally invasive surgical method has the risk of potentially damaging the articular cartilage. Studies have indicated that the destruction of the articular cartilage of finger joints has the inevitable sequelae of pain and stiffness as well as arthritis in finger joints [28,29].…”
Section: Introductionmentioning
confidence: 99%